Lean UX, dai 3-han : ajairu na chīmu ni yoru purodakuto kaihatsu - Gothelf, Jeff (Lean series.)
"In the third edition of this award-winning book, authors Jeff Gothelf and Josh Seiden help you focus on the product experience rather than deliverables. You'll learn tactics for integrating user experience design, product discovery, agile methods, and product management. And you'll discover how to drive your design in short, iterative cycles to assess what works best for businesses and users. Lean UX guides you through this change--for the better."--